Implementasi Tanggung Jawab Hukum Developer terhadap Wanprestasi dalam Perjanjian Pengikatan Jual Beli Perumahan - Sari, Nopita (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The implementation of the Sale and Purchase Binding Agreement (PPJB) in housing transactions frequently gives rise to legal disputes due to delays in the handover of housing units and discrepancies between the agreed specifications and the delivered buildings. This study aims to analyze the implementation of developers' legal liability for breaches of contract arising from the execution of the PPJB. The research employed an empirical juridical method using a descriptive qualitative approach. Primary data were collected through interviews, while secondary data were obtained from legislation, legal literature, and scientific journals. The findings indicate that developers are legally obligated to fulfill all contractual obligations stipulated in the PPJB. Delays in the handover of housing units and discrepancies in building specifications constitute breaches of contract that give rise to legal liability in the form of performance fulfillment and compensation under the Indonesian Civil Code, Law Number 8 of 1999 concerning Consumer Protection, and Law Number 1 of 2011 concerning Housing and Settlement Areas. Strengthening developers' compliance with contractual obligations and enhancing government supervision are essential to ensure legal certainty and consumer protection in housing transactions.